Peran Sektor Swasta dan Partisipasi Masyarakat dalam Pembangunan Ruang Terbuka Hijau (RTH) Berdasarkan Perda No.6 Tahun 2012 tentang Rencana Tata Ruang Wilayah (RTRW) Kota Tangerang 2012-2032 (Studi Kasus: Kecamatan Tangerang) - Kuswati, Sundari; Santosa, Edi; Ghulammanar, Dzunuwanus (Journal of Politic and Government Studies, 2018)
ABSTRACTOne of the concept of development is sustainable, which means the process or development activity is an activity that is carried out on an ongoing basis with the main goal is to meet the needs of human life in order to improve the welfare of man. In carrying out development activities, the Government involves other parties such as private and public. This happens almost every development activity, not least the development of green space in Tangerang. Regulation No. 26 of 2007 concerning spatial explains if every district / city must have green open space at least 30% of its area, with the percentage of 20% of the public green open space which became the responsibility of the Government and 10% Private green open space which became the responsibility of the private sector and the community.Research methods used in this research is the mix method by using the technique of sequential explanatory, this technique is characterized by the data collection and analysis of quantitative data on the first stage, followed by the collection and the analysis of qualitative data at the second stage, in order to strengthen the results of quantitative research in the first stage. Research done in district of Tangerang to the number of samples as much as 68 respondents, with a research instrument using a detailed questionnaire. Researchers also use data results of in-depth interviews with resource-related, as well as other supporting secondary data that comes from books, journals, news media, and sources of other libraries.The results in this study indicate that there is a significant influence of the private sector with a percentage of 10% and the effect of a strong influence on public participation with a percentage of 20.8% influence in the development of open green space in the district of Tangerang. RTH development process will continue to be implemented, so that at the end of a planning period of development (2032) RTH percentage can reach 30% as mandated by law. Increasing the role of the private sector and community participation will continue to be pursued, the regulatory application process improvement will be done so that development planning activities can be run in accordance with what has been organized and planned in the regulation.Â Keyword: Role of the Private Sector, Public Participation, Development of Green Open Space (RTH).